Pengabdian Kepada Masyarakat Program Kemitraan Masyarakat Mandiri (PKM Mandiri) Penyuluhan Cara Menjaga Hidup Bersih Dan Sehat di UPTD SDN 15 Gedong Tataan Kabupaten Pesawaran Tahun 2026 - Linda Barus; Suami (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
School-age children are vulnerable to environmental-based diseases due to suboptimal hygiene practices and inadequate school sanitation. Lack of handwashing habits, maintaining personal hygiene, and choosing safe foods can increase the risk of diarrhea, respiratory infections, worms, and skin diseases. This community service activity aims to increase students' knowledge and awareness regarding clean and healthy living behaviors, personal hygiene, and food hygiene and sanitation. The method used was a one-day counseling through interactive lectures, discussions, educational video screenings, and demonstrations of proper handwashing and tooth-brushing practices. The results of the activity showed an increase in student participation and understanding of the importance of maintaining personal hygiene and the school environment. It was concluded that the counseling was effective in increasing students' knowledge and awareness, so ongoing support is needed so that clean and healthy living behaviors can be implemented consistently at school and at home.